2020
DOI: 10.3233/nre-192993
|View full text |Cite
|
Sign up to set email alerts
|

Dose and staffing comparison study of upper limb device-assisted therapy

Abstract: BACKGROUND: Neurological injuries cause persistent upper extremity motor deficits. Device-assisted therapy is an emerging trend in neuro-rehabilitation as it offers high intensity, repetitive practice in a standardized setting. OBJECTIVE: To investigate the effects of therapy duration and staff-participant configuration on device-assisted upper limb therapy outcomes in individuals with chronic paresis. METHODS: Forty-seven participants with chronic upper extremity weakness due to neurological injury were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Thus, based on the results here, we suggest that an alternative to just increasing the amount of time available to administer COT is to devise technology-based solutions that are scalable and that make it easier and more enjoyable to deliver higher doses and intensities of impairment-focused therapy. 54 It should also be emphasized that even though in this small study we found no significant difference between COT and NAT for delivery of higher doses of intense upper-limb therapy, it does not need to be either/or. It may turn out that the 2 approaches can complement each other.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, based on the results here, we suggest that an alternative to just increasing the amount of time available to administer COT is to devise technology-based solutions that are scalable and that make it easier and more enjoyable to deliver higher doses and intensities of impairment-focused therapy. 54 It should also be emphasized that even though in this small study we found no significant difference between COT and NAT for delivery of higher doses of intense upper-limb therapy, it does not need to be either/or. It may turn out that the 2 approaches can complement each other.…”
Section: Discussionmentioning
confidence: 56%
“…The protocol change would be, as in SMARTS2, to encourage exploratory multi-joint movements outside of a task context for at least two hours a day. Thus, based on the results here, we suggest that an alternative to just increasing the amount of time available to administer COT, is to devise technology-based solutions that make it easier and more enjoyable to deliver higher doses and intensities of impairment-focused therapy 54 . It should also be emphasized, that even though in this small study we found equivalence between COT and NAT for delivery of higher doses of intense upper limb therapy, it does not need to be either/or.…”
Section: Discussionmentioning
confidence: 92%
“…The objective (10) maximizes the total skill acquisition across all patients during the training session, where is the skill improvement function. While function (16) appears slightly different than function (9), this is only because of the difference in the variables used to model the disjunctive and time-indexed models. Both Eqs.…”
Section: Disjunctive Modelmentioning
confidence: 99%
“…To reduce the burden on the therapist, such two-robot setups commonly include automated difficulty adaptation algorithms that aim to keep the exercise difficulty appropriate for both patients [13][14][15], removing the need for the therapist to constantly modify the exercise settings. Short-term studies have shown benefits to such paired rehabilitation such as improved motivation, exercise intensity and motor learning [7][8][9][10][11][12], and a recent clinical trial found greater improvements in functional outcome after paired therapy than after individual therapy [16].…”
Section: Rehabilitation Robotics and The Robotic Gymmentioning
confidence: 99%